# How do you solve 3( y + 4) = 4( y - 6)?

May 24, 2018

Solving for the y-variable gives us $36$.

#### Explanation:

So to solve the multistep equation, we need to use distributive property which gives us:

$3 y + 12 = 4 y - 24$
$3 y + 36 = 4 y$ ----> Adding $24$ to both sides.
$36 = y$ -----> Subtracting $3 y$ from both sides.

But let double check to ensure that this work on both sides.

$3 \left(36 + 4\right)$
$3 \left(40\right)$ ---> Add numbers together inside the parentheses
$120$ ----> Multiplied 40 times 3

$4 \left(36 - 6\right)$
$4 \left(30\right)$ ----> Subtracted numbers together inside the parentheses
$120$ -----> Multiplied 30 times 4.

So since both side of the equal sign is 120, we can say for sure that $y = 36$ is the answer to the equation above.

May 24, 2018

$y = 36$

#### Explanation:

$3 \left(y + 4\right) = 4 \left(y - 6\right)$

first use the distributive property:

$3 y + 12 = 4 y - 24$

$3 y + 36 = 4 y$

subtract 3y from both sides.

$36 = y$

May 24, 2018

$y = 36$

#### Explanation:

Follow the PEMDAS rules: Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction. You solve the equation using those steps in that order.

First, you distribute the three and the four as they're multiplying to the parentheses. You can't do anything more within the parentheses, so then you multiply like so-

$3 \left(y + 4\right) = 4 \left(y - 6\right)$

$3 y + 12 = 4 y - 24$

Then you subtract $3 y$ from both sides

$12 = y - 24$

And finally, to isolate the variable and achieve your answer, you add $24$ to both sides

$y = 36$